2020
DOI: 10.7717/peerj.9136
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and cryopreservation of collared peccary skin-derived fibroblast cell lines

Abstract: Background Biobanking of cell lines is a promising tool of support for wildlife conservation. In particular, the ability to preserve fibroblast cell lines derived from collared peccaries is of significance as these wild mammals are unique to the Americas and play a large role in maintaining the ecosystem. We identified collared peccary fibroblasts by immunofluorescence and evaluated their morphology, growth and adherence capacity. Further, we monitored the viability and metabolic activity of the fibroblasts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Cell-type confirmation is an essential process before cryopreservation. In the present study, the cultures obtained from the ear skin grew with a typical morphology of fibroblasts and expressed intermediate filament protein vimentin ( Figure S1 and Figure 1 ), which confirmed that ear skin can be regarded as a common source of fibroblast separation [ 23 ]. The post-thawing cellular-viability measurement is a key step in the evaluation of the success of cryopreservation.…”
Section: Discussionsupporting
confidence: 77%
“…Cell-type confirmation is an essential process before cryopreservation. In the present study, the cultures obtained from the ear skin grew with a typical morphology of fibroblasts and expressed intermediate filament protein vimentin ( Figure S1 and Figure 1 ), which confirmed that ear skin can be regarded as a common source of fibroblast separation [ 23 ]. The post-thawing cellular-viability measurement is a key step in the evaluation of the success of cryopreservation.…”
Section: Discussionsupporting
confidence: 77%
“…An appropriate cell synchronization protocol in G0/G1 is a crucial step in the development of cloning by SCNT in collared peccaries. Previously, our group developed somatic resource banks aiming at their application in the conservation of this species (Borges et al, 2017(Borges et al, , 2018a(Borges et al, , 2020aLira et al, 2020;Queiroz Neta et al, 2018a). With this new study, we have developed a suitable protocol for somatic cell synchronization, the last step in the preparation of karyoplasts, i.e., somatic nucleus donor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The skin samples were cultured, and four fibroblast lines were previously established (Borges et al, 2020a). Subsequently, cells from four lines frozen in 10% DMSO, 10% FBS and 0.2 M sucrose were thawed, and 4 th and 5 th passage cells were used for this study.…”
Section: Establishment and Culture Of Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panthera onca 10% DMSO, 10% FBS NI [4] Cerdocyon thous 10% DMSO, 50% FBS, 1% ATB-ATM NI [41] Mazama gouazoubira 10% DMSO > 80% [42] Elephas maximus 10% DMSO, 40% FBS > 95.5% [10] Pecari tajacu 10% DMSO, 10% FBS, 0.2 M sucrose > 74.5% [43] Dasyprocta leporina 10% DMSO, 10% FBS > 84.7% [36] Table 2.…”
Section: Solution Employed Viability After Thawing Authorsmentioning
confidence: 99%